Systemic approach to management control through determining factors - Ionel Bostan; Aliona Bîrca; Viorel Ţurcanu; Christiana Brigitte Sandu (Journal of Risk and Financial Management, 2018)
This article aimed to analyse the influence of the main factors on management control used in optimization activities, in order to reach the strategic goals of a company. Agency, transactional costs and contingency theories have been analysed from the traditional perspective. This study reviewed resource-based, institutional, planned behaviour and upper echelon theories, and underlined the main features of management control processes. Empirical evaluation was conducted using data collected from interviews of top management of the main and secondary segments of the Bucharest Stock Exchange. Consequently, we showed the specific features of the systemic approach to management control by means of its determining factors: control environment, management strategies and budgetary system, operational control and the performance appraisal system.
Keywords: 330; control environment; budgetary system and strategies; operational control; company performance